2018
DOI: 10.3892/mmr.2018.8563
|View full text |Cite
|
Sign up to set email alerts
|

TRP‑2 mediates coat color pigmentation in sheep skin

Abstract: Tyrosinase-related protein 2 (TRP-2) is one of the most important members of the tyrosinase family, and is a key enzyme involved in melanin biosynthesis. In the present study, a skin transcriptome profile, immunohistochemistry, western blotting and reverse transcription-quantitative polymerase chain reaction were used to investigate TRP-2 expression in sheep with different coat colors, namely, black, white and black-white. TRP-2 was overexpressed in melanocytes in order to study the effect of TRP-2 on melanin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…TYRP1 also maintains TYR stability, regulates TYR catalytic activity, and plays a part in melanocyte maturation, proliferation, and apoptosis [19,20]. In previous studies, black animals showed higher levels of TYR, TYRP1, and DCT than white animals [21][22][23]. Our results showed that, during the production of the black substance in the breeding season, TYR, TYRP1, and DCT were upregulated in black skin, indicating that eumelanin is likely an important component of the black substance.…”
Section: Melanin Synthesis and Transportsupporting
confidence: 59%
“…TYRP1 also maintains TYR stability, regulates TYR catalytic activity, and plays a part in melanocyte maturation, proliferation, and apoptosis [19,20]. In previous studies, black animals showed higher levels of TYR, TYRP1, and DCT than white animals [21][22][23]. Our results showed that, during the production of the black substance in the breeding season, TYR, TYRP1, and DCT were upregulated in black skin, indicating that eumelanin is likely an important component of the black substance.…”
Section: Melanin Synthesis and Transportsupporting
confidence: 59%
“…Past research shows that tyrosinases can catalyze the first two steps of melanin production and are associated with hyperpigmentation disorders such as melasma, solar lentigines, and postinflammatory hyperpigmentation (Fisk, Agbai, Lev‐Tov, & Sivamani, ; Xue et al, ). Plants that contain natural active ingredients can reduce melanin synthesis through inhibiting tyrosinases and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinases catalyze the ortho‐hydroxylation of tyrosine to dihydroxy‐phenyl‐alanine (DOPA) and the subsequent two‐electron oxidation to dopaquinone (Rolff et al, ). They are also related to enzymatic browning in fruit and vegetables, pigmentation, and insect physiological processes (Balabanidou, Grigoraki, & Vontas, ; Olmedo et al, ; Xue et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Skin pigmentation in animals is a polygenic trait, and may be influenced by different kinds of multi-gene interactions ( Barsh, 1996 ). The proteins and genes associated with skin color in humans, mice, chickens, and sheep include agouti signaling protein (ASIP) ( Lu et al, 1994 ), melanocyte-stimulating hormone receptor (MSH) ( Robbins & Nadeau, 1993 ), microphthalmia transcription factor (MITF) ( Dong, Yoshiaki & Vijayasaradhi, 2002 ; Vetrini et al, 2004 ; Wang et al, 2018 ), tyrosinase (TYR) ( Deng et al, 2008 ; Yu et al, 2017 ), tyrosinase-related protein-1 (TYRP1) ( Chun et al, 2016 ), dopachrome tautomerase (DCT) ( Xue et al, 2018 ), melanocortin 1 receptor (MC1R) ( Fontanesi et al, 2010 ; Bourgeois et al, 2016 ; Wolf Horrell, Boulanger & D’Orazio, 2016 ), solute carrier family 45 member 2 (SLC45A2) ( Wang et al, 2016 ), and others. There are over 100 known color loci in mice and many of them have been cloned and sequenced ( Bennett & Lamoreux, 2003 ).…”
Section: Introductionmentioning
confidence: 99%